Evaluación de la toxicidad de cobre en suelos a través de biomarcadores de estrés oxidativo en eisenia foetida - Gaete,Hernán (2010)
Copper toxicity in soil was evaluated using biomarkers of oxidative stress (catalase enzyme activity, superoxide dismutase and lipid peroxidation) in the earthworm Eisenia foetida. Agricultural topsoils from mining areas of the Aconcagua river basin were collected. Total copper concentrations were in the range of 94-959 mg kg-1, while the exchangeable copper concentrations were in the range of 46-2225 µg kg-1. Earthworms exposed to soil with exchangeable copper concentrations above 32 µg kg-1 showed an increase in catalase activity. Parameters of antioxidant activity were more sensitive than the weight change and thus can be used as appropriate biomarkers in Eisenia foetida.